Answer:
The solution is
![x=(9)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gqloyp2lo99omgj7wrpkr8tmudlor5p90b.png)
![y=(17)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/agqcbmfuwjz7j51nu1r3b3ak0iezril8cj.png)
Explanation:
We have the system:
-4x+6y=6
-7x+5y=2
I would like to solve this by elimination because I don't feel like rearranging both equations and they both have the same form which is crucial in elimination. The only thing is I will need opposites in a column (where the variable are).
So I'm going to focus on the x's. I want the x part to be opposites.
I know if I multiply the first equation by 7 I will get -28x plus... and if I multiply the last equation by -4 I will get 28x plus... .
28x and -28 are opposites and we all know what happens to opposites when you add them. They zero out; cancel out. That is -28x+28x=0.
So let's multiply first equation by 7 and
multiply bottom equation by -4:
-28x+42y=42
28x-20y=-8
----------------------We are ready to add the equations:
0+22y=34
22y=34
Divide both sides by 22:
y=34/22
Reduce the fraction:
y=17/11 (I divided top and bottom by 2.)
Now if y=17/11 and -4x+6y=6, we can find x by inserting 17/11 for y in the second equation I wrote in this sentence.
![-4x+6\cdot (17)/(11)=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/le1k6ucu0t376zhqfv9r0nnqo5hy0wuto2.png)
Perform the simplification/multiplication of 6 and 17/11:
![-4x+(102)/(11)=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mg69mba2csjb4corvd0gxlzvmgeg570rp7.png)
Subtact 102/11 on both sides:
![-4x=6-(102)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l9jbjf2pptbfj5efk11ybja5hmogljoei6.png)
Find a common denominator:
![-4x=(66)/(11)-(102)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lo1f0yj91o4v16efi6995bap8l3lwfngzp.png)
![-4x=(-102+66)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/adlsa20qj9vlp2n2uz6ozrli7pshqqlajh.png)
![-4x=(-36)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3qgb005v2ib9iyurv71g15gwng7r1sjv9l.png)
Divide both sides by -4:
![x=(-36)/(-4(11))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wrjz6sjhtkqskcax51peiop2adj4llxfvp.png)
Reduce 36/4 to 9:
![x=(9)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gqloyp2lo99omgj7wrpkr8tmudlor5p90b.png)
![x=(9)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gqloyp2lo99omgj7wrpkr8tmudlor5p90b.png)
The solution is
![x=(9)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gqloyp2lo99omgj7wrpkr8tmudlor5p90b.png)
![y=(17)/(11)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/agqcbmfuwjz7j51nu1r3b3ak0iezril8cj.png)